The BIALL Conference 1970 to 2019. (June 2019) - Bowl, Catherine; Furlong, John; Mosley, Caroline
Abstract: In this article, the authors, Catherine Bowl, John Furlong and Caroline Mosley look at the direction the Association's Annual Conference has taken over the past 50 years since the first Conference in Liverpool in 1970. The emphasis is on the mid-1990s to the present day, during which period the authors served as Chairs of BIALL's Conference Committee 1 .